SYNTHESIS AND CHARACTERIZATIONS OF STARCH-G-POLY(POTASSIUM 3- SULFOPROPYL METHACRYLATE) AS PICKERING EMULSION STABILIZER - Dzakia, Alya
Emulsions have important roles in food industry. The development of emulsions continues to be carried out to improve safety, multifunctionality and stability of emulsions. Pickering emulsion stabilized by solid particles can answer these needs with its superior properties compared to conventional emulsions. Starch, with its abundant presence, is one of the biomolecules used as a stabilizer for Pickering emulsions. The nature of starch is generally hydrophilic and has many hydrogen bonds. However, its low solubility in water will result in the formation of aggregates so that modifications are needed to increase its surface activity and stability capabilities. The development of starch modification with an anionic monomer, namely potassium 3-sulfopropyl methacrylate via the graft copolymerization method can be a solution to this problem. This modification provides a strong spatial barrier to prevent droplet coalescence at the oil water interface. In this research, starch was obtained from the isolation of cassava plants with a yield of 9.4% (w/w). The starch modification process is carried out using microwaves in a nitrogen atmosphere. The product in this research was starch-g poly(potassium 3-sulfopropyl methacrylate), which was varied at theoretical degrees of polymerization (DPn) of 10, 20, 40, and 60. The yield for each theoretical DPn was 58,6%; 54,7%; 76,6%; and 70,0% (w/w), and the grafting percentage was respectively 328%, 645%, 1913%, and 2624%. Based on FTIR characterization of starch-g- poly(potassium 3-sulfopropyl methacrylate) product, a new peak was obtained at a wave number of 1700 cm??, which indicates C=O stretching vibration. XRD characterization shows typical 2? peaks at 17,4º and 25º from potassium 3-sulfopropyl methacrylate monomer and have amorphous properties like starch. Based on visual observation tests of the Virgin Coconut Oil (VCO) emulsion system in water with a volume ratio of 1:9, it was known that starch-g-poly(potassium 3-sulfopropyl methacrylate) with theoretical DPn 60 provides the most stable results. This stability is measured against time, storage temperature, shock, and certain pH conditions. Particle Size Analyzer characterization shows a decrease in the diameter of the emulsion droplets as the pH increases. Based on zeta potential analysis, it was found that the surface charge of the emulsion was increasingly negative at higher pH. Critical micelle concentration values for theoretical DPn 40 and 60 were respectively obtained at concentrations of 0,25% and 0,40% (w/v).